Proposal for improvement in the logistics area on operating costs of Bermanlab S.A.C. Trujillo, 2020 [Propuesta de mejora en el área de logística sobre los costos operativos de Bermanlab S.A.C. Trujillo, 2020] - Angulo-Noel, Brenda (2021)
This work was prepared to develop an improvement proposal for Bermanlab logistics area through the application of engineering tools to reduce operational costs. In the first place, the existing problems in the area were identified, an Ishikawa diagram was used for the diagnosis where the causes of these problems are exposed. It was proposed to use the Kardex tools, 5S and the EOQ model for the solution. Which can reduce operating costs by S /. 9,368.16. Finally, an economic evaluation was carried out, which would have a VAN of S /. 11,987.15, an TIR of 92.95% and a B / C of S /. 2.45, concluding that the proposal would be profitable.